QTL Analysis of Transgressive Nematode Resistance in Tetraploid Cotton Reveals Complex Interactions in Chromosome 11 Regions - Wang, Congli; Ulloa, Mauricio; Duong, Tra T.; Roberts, Philip A. (Frontiers in Plant Science, 2017)
Transgressive segregation in cotton (Gossypium spp.) provides an important approach to enhance resistance to the major pest root-knot nematode (RKN) Meloidogyne incognita. Our previous studies reported transgressive RKN resistance in an intraspecific G. hirsutum resistant NemX x susceptible SJ-2 recombinant inbred line (RIL) population and early generations of interspecific cross G. barbadense (susceptible Pima S-7) x G. hirsutum (NemX). However, the underlying functional mechanisms for this phenomenon are not known. In this study, the region of RKN resistance gene rkn1 on chromosome (Chr) 11 and its homoeologous Chr 21 was fine mapped with G. raimondii D5 genome reference sequence. Transgressive resistance was found in the later generation of a new RIL population F2:7 (Pima S-7 x NemX) and one interspecific F2 (susceptible Pima S-7 x susceptible SJ-2). QTL analysis revealed similar contributions to root-galling and egg-production resistance phenotypes associated with SSR marker CIR316 linked to resistance gene rkn1 in NemX on Chr 11 in all seven populations analyzed. In testcross NemX x F1 (Pima S-7 x SJ-2) marker allele CIR069-271 from Pima S-7 linked to CIR316 contributed 63% of resistance to galling phenotype in the presence of rkn1. Similarly, in RIL population F2:8 (NemX x SJ-2), SJ-2 markers closely linked to CIR316 contributed up to 82% of resistance to root-galling. These results were confirmed in BC1F1 SJ-2 x F1 (NemX x SJ-2), F2 (NemX x SJ-2) and F2 (Pima S-7 x SJ-2) populations in which up to 44%, 36% and 15% contribution in resistance to galling was found, respectively. Transgressive segregation for resistance was universal in all intra- and inter-specific populations, although stronger transgressive resistance occurred in later than in early generations in the intraspecific cross compared with the interspecific cross. Transgressive effects on progeny from susceptible parents are possibly provided in the rkn1 resistance region of chromosome 11 by tandemly arrayed allele (TAA) or gene (TAG) interactions contributing to transgressive resistance. Complex TAA and TAG recombination and interactions in the rkn1 resistance region provide a three-gene model to study disease and transgressive resistance in polyploid plants, and novel genotypes for plant breeding.